PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR DAN KEAKTIFAN SISWA PADA MATA PELAJARAN IPA KELAS V SDN 3 DOKORO WIROSARI - Friesca Candra Arenita; Prasetiyo Prasetiyo; M. Arief Budiman (Universitas Negeri Medan, 2018)
Abstract: The Influence of Numbered Head Together (NHT) Learning Models on Learning Outcomes and Student Activity in Science Subjects in Class V State Elementary School 3 Dokoro Wirosari. This study aims to determine the significant effect of Numbered Head Together (NHT) learning models on learning outcomes and student learning activeness in science subjects in grade V of Dokoro 3 State Elementary School. This type of research is a quantitative research in the form of Pre-Experimental Design with the type of One Group Pretest-Posttest. The population of this study were all students in grade V SDN 3 Dokoro 2017/2018. The sample taken was 20 students. The data in this study were obtained through tests, documentation, and questionnaires. Based on the results of the study it can be concluded that Ha is accepted, meaning the Numbered Head Together learning model has an effect on learning outcomes and active learning of science in fifth grade students of Dokoro 3 State Elementary School.Keyword: Numbered Head Togegther, Learning outcomes, Learning activenessAbstrak: Pengaruh Model Pembelajaran Numbered Head Together (NHT) Terhadap Hasil Belajar dan Keaktifan Siswa pada Mata Pelajaran IPA Kelas V SDN 3 Dokoro Wirosari. Penelitian ini bertujuan untuk mengetahui pengaruh yang signifikan model pembelajaran Numbered Head Together (NHT) terhadap hasil belajar dan keaktifan belajar siswa pada mata pelajaran IPA kelas V Sekolah Dasar Negeri 3 Dokoro. Jenis penelitian ini adalah penelitian kuantitatif dalam bentuk Pre-Eksperimental Design dengan jenis One Group Pretest-Posttest. Populasi penelitian ini adalah seluruh siswa kelas V SDN 3 Dokoro 2017/2018. Sampel yang diambil adalah 20 siswa. Data dalam penelitian ini diperoleh melalui tes, dokumentasi, dan angket. Berdasarkan hasil penelitian dapat disimpulkan bahwa Ha diterima, artinya model pembelajaran Numbered Head Together berpengaruh terhadap hasil belajar dan keaktifan belajar IPA siswa kelas V Sekolah Dasar Negeri 3 Dokoro.Kata Kunci: Numbered Head Togegther, Hasil belajar, Keaktifan belajar